2009
DOI: 10.1073/pnas.0905103106
|View full text |Cite
|
Sign up to set email alerts
|

Mediator complex association with constitutively transcribed genes in yeast

Abstract: Mediator is a large, multisubunit complex that is essential for transcription of mRNA by RNA Pol II in eukaryotes and is believed to bridge transcriptional activators and the general transcription machinery. However, several recent studies suggest that the requirement for Mediator during transcriptional activation is not universal, but rather activator dependent, and may be indirect for some genes. Here we have investigated Mediator association with several constitutively transcribed genes in yeast by comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
76
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 49 publications
(83 reference statements)
8
76
0
Order By: Relevance
“…5,8,41 Previous studies in our lab have shown that the loss of Mediator head and middle modules from several constitutive as well as inducible gene promoters in med17/srb4 ts mutant yeast leaves the tail module associated with these promoters. 23,41 However, the loss of head and middle modules in this mutant resulted in greatly reduced binding of RNAP II, TBP and other GTFs to all RNAP II transcribed genes examined, 23 consistent with loss of transcription of almost all RNAP II transcribed genes in this mutant. 9 The tail module, however, might be able to function independently in early steps of PIC formation such as recruitment of SAGA or Swi/Snf complex and chromatin remodeling.…”
Section: Independent Recruitment and Function Of Med15/med3/med2mentioning
confidence: 93%
See 1 more Smart Citation
“…5,8,41 Previous studies in our lab have shown that the loss of Mediator head and middle modules from several constitutive as well as inducible gene promoters in med17/srb4 ts mutant yeast leaves the tail module associated with these promoters. 23,41 However, the loss of head and middle modules in this mutant resulted in greatly reduced binding of RNAP II, TBP and other GTFs to all RNAP II transcribed genes examined, 23 consistent with loss of transcription of almost all RNAP II transcribed genes in this mutant. 9 The tail module, however, might be able to function independently in early steps of PIC formation such as recruitment of SAGA or Swi/Snf complex and chromatin remodeling.…”
Section: Independent Recruitment and Function Of Med15/med3/med2mentioning
confidence: 93%
“…20 In contrast, TFIIDdependent genes, many of which may not require Swi/Snf, could depend on Mediator subunits other than those in the tail module to interact with activators or TFIID components, thus leading to the interactions with other GTFs and formation of PIC. [23][24][25] In summary, although connections between the Mediator tail, Swi/Snf and SAGA have been established, the detailed mechanisms behind these interconnections likely differ at different promoters, and an understanding of the precise molecular basis underlying these connections remains to be achieved.…”
Section: Tail Module Specificity For Saga/ Swi-snf Dependent Promotersmentioning
confidence: 99%
“…21,22 A global regulator of transcription is the Mediator complex. 23,24 At pre-initiation complexes (PICs) Mediator conveys the activating signals from enhancers to promoters via interacting with both transcription factors and the basal transcriptional machinery. [25][26][27] Two major forms of Mediator complexes have been identified by mass spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The Mediator core contains more than 20 subunits organized into head, middle, and tail modules (Guglielmi et al, 2004;Chadick and Asturias, 2005). This core associates with the RNAPII complex to form the holoenzyme, stimulating basal transcription and supporting the activation of transcription by specific transcription activators (Mittler et al, 2001;Baek et al, 2002;Zhu et al, 2006;Ansari et al, 2009). Individual Mediator subunits converge diverse signals to the RNAPII transcription complex via interaction with a particular or a class of transcription activators, leading to pathway-specific gene transcription (Balamotis et al, 2009;Kagey et al, 2010;Takahashi et al, 2011).…”
mentioning
confidence: 99%